Oral Squamous Cell Carcinoma: Challenges in Treatment for Low- and Middle-Income Countries: Fetching towards the far Ahead Horizon (London Journal of Medical and Health Research, 2024)
This perspective article discusses the origin of tobacco, its spread and the changes it produces in human body, most prevalent of which it is oral squamous cell carcinoma. Especially in low-and middle -income countries, where the use of tobacco is already trend setting and concomitant cases are also increasing, so some simpler measures should be needed to implement which can reduce the size of the lesion and the lymph node shrink from the original size so that it prevents not only the load of reconstruction, but might also lead to improved mortality outcomes.
Keywords: Vanoxerine consta; Stimulant (Amphetamine-Type Substances/ATS) dependence; long-term delivery; PLGA polymers; enzymes.; collagenase; recombinant.; Skin flaccidity; sagging skin; hyaluronic acid; quality; Efficiency; Optimization; Turnaround time; appointment schedule; Affects; predictive coding; simulation; Markovblanket; RSI paradigm.